'A blank page … ' or 'Ten years since language left … ' (Artaud). (4th July 2021) - Twitchin, Mischa
Abstract : In his copy of the published text of Artaud the Mômo, Artaud added a note for a future edition that invokes 'a blank page to separate the text of the book, which is finished from all the swarming of Bardo which appeared in the limbo of electroshock'. What is at stake in this separation, this interruption, in the time of reading Artaud? What kind of testimony to the necropolitics of modernity might be offered by the interruption provided by this anticipated blank page? Artaud wanted his testimony to existence to interrupt the induced death to which he felt subject—to bear witness, on the one hand, to the living death (or Bardo) that society demands of those who claim not to suffer from 'alienation', and, on the other, to the 'authentic madmen' who are 'suicided by society'. The issue is not, of course, to write on or over the blank page, but to engage with what is written around it—reflecting on the return of Artaud the Mômo; a return understood to herald that transformation of the body that Artaud evokes after the 'ten years in which language left' him. His projected interruption in reading the Mômo text tries to turn back on society an awareness of relations between the living and the dead that it would prefer to ascribe to madness. Such relations remain of profound concern, however, as evidenced, for example, in Anne Boyer's recent discussion of what she identifies as the 'industrialised world's carcinogenosphere'.